2016
DOI: 10.1021/acssuschemeng.6b01466
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of a Semi-interpenetrating Polymer Network Slow-Release Nitrogen Fertilizer with Water Absorbency from Cotton Stalks

Abstract: A semi-interpenetrating polymer network (semi-IPN) slow-release nitrogen fertilizer with water absorbency was synthesized via microwave irradiation. Urea was incorporated as the nitrogen source into a cotton stalk-g-poly(acrylic acid)/ bentonite (CS-g-PAA/bent) network and linear polyvinylpyrrolidone (PVP). A reaction mechanism for synthesis of CS-g-PAA/ bent/PVP/urea was proposed. Variables influencing water absorbency, such as microwave power, irradiation time, and contents of CS, PVP, and bent were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…The results indicated that Matador and Nitrophoska have good slow-release compound fertilizers which provided an efficient way of supplying trees with essential elements to growth especially under sandy soil conditions such as Nubaria region which is characterized with poor fertility, low water holding capacity, and easily leaching of nutrients from the soil as well as to prevent environmental pollution compared with fast-release mineral fertilizer and cost-saving, thus can efficiently improve the utilization efficiency of fertilizers. These results are in accordance with those obtained by Wen et al (2016); slow-release fertilizers may be a promising approach to alleviate such problems and improve nutrient utilization efficiency at the same time directly through its design at form releases the nutrients gradually at the rate in accordance with the nutrient requirement of the plants, which is conducive to the reduction of nutrient loss (Teodorescu et al, 2009). Also they gave the highest values of residual elements in soil due to their low activity index, compared with the fastrelease mineral fertilizer which gave the lowest values of available elements left in the soil (Mikkelesen et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that Matador and Nitrophoska have good slow-release compound fertilizers which provided an efficient way of supplying trees with essential elements to growth especially under sandy soil conditions such as Nubaria region which is characterized with poor fertility, low water holding capacity, and easily leaching of nutrients from the soil as well as to prevent environmental pollution compared with fast-release mineral fertilizer and cost-saving, thus can efficiently improve the utilization efficiency of fertilizers. These results are in accordance with those obtained by Wen et al (2016); slow-release fertilizers may be a promising approach to alleviate such problems and improve nutrient utilization efficiency at the same time directly through its design at form releases the nutrients gradually at the rate in accordance with the nutrient requirement of the plants, which is conducive to the reduction of nutrient loss (Teodorescu et al, 2009). Also they gave the highest values of residual elements in soil due to their low activity index, compared with the fastrelease mineral fertilizer which gave the lowest values of available elements left in the soil (Mikkelesen et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…The resin showed good water absorbency of 198.5 g/g in distilled water and 26.3 g/g in 0.9 wt% NaCl solution. Similarly, a semi‐IPN polymer network (CS‐g‐PAA/bent/PVP/urea) for slow‐release nitrogen fertilizer reported by Wen et al also presented outstanding slow‐release performances and the excellent water absorbency of 1018.4 g/g in distilled water and 71.3 g/g in 0.9 wt% NaCl solution . Obviously, the technology brings a convenient method for preparing multi‐component polymer materials and a flexible strategy to improve the properties of natural polymer‐based resins.…”
Section: Introductionmentioning
confidence: 99%
“…The industry of fertilizers must increase the efficiency of its products, improving or developing new types of fertilizers to avoid or reduce environmental pollution. It is considered that an ideal fertilizer should have at least three characteristics: a high percentage of recovery and production; a minimum negative impact on the environment and with a single application of the product should be enough to cover the nutritional requirements during the entire culture period [9][10][11][12][13][14]. According to these characteristics, Slow Release Fertilizers (SRF) have a relevance nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…The obtention of SRF constitutes a technology that meets the three characteristics of an ideal fertilizer. The use of SRF helps preventing soil degradation, can be used to reduce the amount of fertilizer that is applied and make the nutrients available for longer periods of time after application, since they avoid losses due to leaching and volatilization of the fertilizer [3,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%